2018
DOI: 10.1017/jfm.2017.884
|View full text |Cite
|
Sign up to set email alerts
|

Flow past finite cylinders of constant curvature

Abstract: Wake visualization experiments were conducted on a finite curved cylinder whose plane of curvature is aligned with the free stream. The stagnation face of the cylinder is oriented concave or convex to the flow at $230\leqslant Re_{D}\leqslant 916$, where $Re_{D}$ is the cylinder Reynolds number and the curvature is constant and ranges from a straight cylinder to a quarter-ring. While the magnitude of the local angle of incidence to the flow is the same for both orientations, the contrast in their wakes demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…Similar large shedding angles are also reported in Ref. [5], although its experimental research considered different configurations (radius of curvature R/D = 19 and 38, compared to R/D = 12.5 in the present study).…”
Section: Influence Of the Vertical Extensionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar large shedding angles are also reported in Ref. [5], although its experimental research considered different configurations (radius of curvature R/D = 19 and 38, compared to R/D = 12.5 in the present study).…”
Section: Influence Of the Vertical Extensionsupporting
confidence: 91%
“…We therefore conclude that one may need at least a 21D long vertical extension at Re = 200 to get a reliable wake for this configuration. Although a parallel shedding regime is not observed in the VE studies, as proposed in earlier studies [5], we would expect it to appear if the vertical extension is further increased (and the axial velocity disappears). In the present study, we have observed that the axial velocity can be as high as 20% of the free-stream velocity U 0 at z/D = 20, at Re = 200.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations